The Effect of Stimulated Brillouin Scattering on WDM-PON - Ļašuks, I. (Elektronika ir Elektrotechnika, 2010)
The existing TDM-PON (Time-Division Multiplexing Passive Optical Network) technologies like EPON (Ethernet PON) or GPON (Gigabit PON) have limitations of bandwidth due to the concept of time division .The bit rate can only be enlarged increasing the speed of the common channel (10G EPON). Another way of achieving the bandwidth growth is the use of WDM (Wavelength Division Multiplexing) technology .The main problem of the WDM-PON is the ability to use the existing cable plant with high losses due to power splitters. Hybrid TDM/WDM-PON conception is the only way of upgrading of the existing technologies. However, there is a lack of power budget to enlarge a number of wavelengths and the splitting ratio. The easiest way of enlarging the power margin is the increase of inserted power. The main limitation is SBS (Stimulated Brillouin Scattering), which scatters all the power after the threshold. The paper contains: SBS threshold measurement and comparison with theoretical data, the evaluation On-Off Keying effect on SBS threshold, calculation of maximum power budget and channel (client) number limited by SBS for 16-channel TDM/WDM-PON system based on SBS threshold measurement data.